Effect of heat treatment temperature on the microstructure and wear corrosion properties of NiCrBSi–TiN composite coatings. Issue 5 (1st March 2022) - Wang, YuXin; Jiang, Jie; Chi, YunLong; Mao, XingYe; Zhu, LinLin; Dong, YanChun; Yang, Yong; He, JiNing
Abstract: For this study, NiCrBSi–TiN composite coatings were fabricated on Q235 steel substrates by reactive plasma spraying and the coatings were heat treated at 600 °C, 700 °C, 750 °C and 800 °C for 1 h. The microstructure evolution of these coatings untreated and treated at different temperatures was analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM) combined with energy dispersive spectroscopy (EDS) and transmission electron microscopy (TEM). The hardness of the coatings was characterised using the Weibull distribution while the wear and corrosion resistance were studied using a block-ring tribometer and an electrochemical workstation. The phase composition of coatings after heat treatment changed, the compactness of coatings was increased, and the interlayer bonding was significantly improved. Comprehensive experimental results illustrated that the performance of the NiCrBSi–TiN composite coatings was excellent at the heat treatment temperature of 700 °C.